'A fraud, a drunkard, and a worthless scamp': estate agents, regulation, and Realtors in the interwar period. Issue 5 (4th July 2017) - Latham, Mark
Abstract: The estate agency industry played a key role in the growth of the interwar property market. An important feature of the industry was the low barriers to entry, particularly in terms of regulating practitioners. Yet repeated attempts were made to introduce mandatory licensing of estate agents during this period, all of which failed. This article explores why these attempts were instigated, by whom, and why they failed. It utilises the comparison with the successful introduction of licensing for real estate brokers in the US. The article argues that the desire for a professional identity fuelled these regulatory efforts, and that industry specific endogenous tensions led to their failure. In doing so, this article informs our knowledge of both the interwar development of this key service industry, and of the concepts used to analyse regulation more generally.